RESEARCH PROJECTS IN ACCOUNTING . - Jones, Ralph Coughenour (The Accounting Review, 1951)
This article focuses on the research projects in accounting. Last published list of accounting theses appeared in the September, 1941, issue of the journal "The Accounting Review," nearly ten years ago. Comments of a number of members during recent months suggest that there is a considerable demand for information about accounting research currently in progress. The questionnaires called for the classification of titles under eighteen subject headings. The present list is offered in partial fulfillment of that demand. Accounting for Corporate Capital Transactions, Rufus Wixon, University of Michigan, Ann Arbor, Michigan. The Accounting Determination of Income, Joseph A. Silveso, University of Missouri, Missouri. Effect of Inflation on Accounting Literature, Robert H. Shutt, University of Texas, Arlington, Texas. The Effect of the Decline in the Economic Value of the Monetary Unit upon Accounting for Fixed Assets, Raymond Lee Gibbs, Southern Methodist University, Dallas, Texas. Accounting for Organization Expense, George W. Underwood, University of Tulsa, Tulsa, Oklahoma. Accounting for the Acquisition and Amortization of Goodwill, Harry Richard Hedlund, State University of Iowa, Ames, Iowa.